Review of Wiktoria Kudela-Świątek. Eternal Memory: Monuments and Memorials of the Holodomor - Simone Attilio Bellezza (East/West: Journal of Ukrainian Studies)
Review of Wiktoria Kudela-Świątek. Eternal Memory: Monuments and Memorials of the Holodomor. Translated from the Polish by Guy Russell Torr, preface by Frank E. Sysyn, Canadian Institute of Ukrainian Studies P in co-operation with Wydawnictwo Księgarnia Akademicka, 2021. 410 pp. Illustrations. Bibliography. List of Illustrations. Index. $43.95, paper.